Peran Filsafat Pendidikan dalam Menghadapi Tantangan Pendidikan Modern - Wulandari Berliana Sapyudin; Shobrun Jamil; Amalia Ramadhani; Fakhita Fakhita (Indo Publishing, 2026)
Educational philosophy plays a crucial role in providing a foundation for thought, direction, and values ​​in the implementation of education, particularly in the modern era marked by technological developments and globalization. This study aims to analyze the role of educational philosophy in addressing the various challenges of modern education. The method used is a literature study by reviewing various relevant literature sources. The results of the study indicate that modern education faces various challenges, such as disparities in access to education, a cultural identity crisis, the negative impacts of technological development, and a decline in students' moral values. In this context, the philosophy of education functions as a basis for thinking that can be used as a guideline, filtering out the negative impacts of developments, and strengthening moral and spiritual principles in the educational process. Furthermore, educational philosophy also helps shape educators who possess moral responsibility and critical thinking skills. Therefore, educational philosophy remains highly relevant and necessary to maintain the quality and goals of education in the modern era